Meta-analisis Implementasi Pemilihan Umum Anggota DPR, DPD, dan DPRD Provinsi, Kabupaten, dan Kota - Tasrin, Krismiyati (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2008)
In 2004, Indonesian hold a direct election for the first time. Many complements came from international for succesfull direct election we had. Besides some points about unsuccess story related to implementation direct election to elect representatives council both DPR and local representative council named DPRD (province and city/regional). Those important points are unvalid paricipants data, late logistic distribution, and money politics. To know this conditions, evaluation the content of direct election policy and implementation for DPR, DPD and DPRD is the most strategic step to increase the performance of direct election for the future.